Positive rate of Southeast Asian Ovalocytosis (SAO) among patients sent for thalassemia diagnosis from Naradhiwas Rajanagarindra hospital - Kawon, Watcharaphong; Yamsri, Supawadee; Fucharoen, Goonnapa; Duereh, Amara; Fucharoen, Supan (Archives of Allied Health Sciences, 2019)
Southeast Asian Ovalocytosis (SAO) and thalassemia are inherited red blood cell disorders causing hemolysis. A high prevalence of SAO has been found in southern Thailand where thalassemia is common. Therefore, patients with co-inheritance of these two genetic abnormalities can be encountered. In this study, SAO was screened in patients at Naradhiwas rajanagarindra hospital whose blood specimens were obtained at the Centre for Research and Development of Medical Diagnostic Laboratories, Khon Kaen University for thalassemia diagnosis. Gap-PCR analysis was used to identify the SAO mutation. From 326 subjects examined, 21 had SAO mutation (6.4%; 95% CI = 4.0-9.6). Two hundred ninety-two subjects carried thalassemia gene (89%), the most common one (n=107) was hemoglobin E. Out of these 107 subjects, eight were positive for SAO. Comparison of red blood cell parameters between these two groups showed higher MCV, MCH and RDW values in those with SAO as compared to those without SAO. This data indicated a high opportunity to find co-inheritance of SAO and thalassemia in the region. The increased MCV value with this combined defects would further alter thalassemia screening. Without clinical data, it is however difficult to draw any effect of SAO on the clinical presentation of thalassemia and hemoglobinopathies. Further study in collaboration with clinicians is required to provide additional information related to this matter